Effect of polyunsaturated fatty acids (PUFAs) on the proliferation and extracellular matrix mineralization and gene expression of gilthead seabream skeletal cell lines - Viegas, Michael (2015)
The aquaculture industry aims at replacing significant amounts of marine fish oil by vegetable oils in fish diet. Dietary lipids have been shown to alter the fatty acid composition of bone compartments, which would impact the local production of factors controlling bone formation. Knowledge on the mechanisms underlying the nutritional regulation of bone metabolism is however scarce in fish. Two in vitro bone-derived cell systems developed from seabream (an important species for aquaculture in the Mediterranean region) vertebra, capable of in vitro mineralization and exhibiting prechondrocyte (VSa13) and pre-osteoblast (VSa16) phenotype, were used to assess the effect of certain polyunsaturated fatty acids (PUFAs; arachidonic (AA), eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids) on cell proliferation, extracellular matrix (ECM) mineralization and gene expression. While all PUFAs promoted morphological changes in both cell lines, VSa16 cell proliferation appeared to be stimulated by PUFAs in a dose dependent manner until 100M, whereas proliferation of VSa13 cells was impaired at concentrations above 10M. AA, EPA and DHA inhibited VSa13 ECM mineralization, alone and in combination, while VSa16 ECM mineralization was only inhibited by AA and EPA. DHA had the opposite effect, increasing mineralization almost by 2 fold. When EFAs were combined, DHA apparently compensated for the inhibitory effect of AA and EPA. Expression of marker genes for bone and lipid metabolisms has been investigated by qPCR and shown to be regulated in pre-osteoblasts exposed to individual PUFAs. Our results show that PUFAs are effectors of fish bone cell lines, altering cell morphology, proliferation and mineralization when added to culture medium. This work also demonstrates the suitability of our in vitro cell systems to get insights into mineralization-related effects of PUFAs in vivo and to evaluate the replacement of fish oils by vegetable oil sources in fish feeds.